2018
DOI: 10.1016/j.impact.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Inter-laboratory comparison of nanoparticle size measurements using dynamic light scattering and differential centrifugal sedimentation

Abstract: Inter-laboratory comparison of nanoparticle size measurements using dynamic light scattering and differential centrifugal sedimentation. NanoImpact, (2018).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 46 publications
1
51
0
Order By: Relevance
“…The standardization of characterization methods to monitor the physicochemical properties before and after NPs' dispersion is also work in progress, e.g., by the OECD Series on the Safety of Manufactured Nanomaterials [58] and ISO/TC229 (Nanotechnologies), and has been subject of several ILC studies. Remarkably, in ILC studies in which model nanoparticles as polystyrene, gold or silica nanospheres have been used, for example those looking at size distribution measurements using nanoparticle tracking analysis [61], dynamic light scattering and centrifugal particle sedimentation [49], similar issues in reproducibility compared to our study have been reported, even for simple dispersions in buffer. They concluded that SOPs are indispensable for obtaining reliable and comparable NP size data, and should be tailored to the specific test system, sufficiently detailed and verified by a larger number of laboratories, to enable reproducible performance [49,61].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The standardization of characterization methods to monitor the physicochemical properties before and after NPs' dispersion is also work in progress, e.g., by the OECD Series on the Safety of Manufactured Nanomaterials [58] and ISO/TC229 (Nanotechnologies), and has been subject of several ILC studies. Remarkably, in ILC studies in which model nanoparticles as polystyrene, gold or silica nanospheres have been used, for example those looking at size distribution measurements using nanoparticle tracking analysis [61], dynamic light scattering and centrifugal particle sedimentation [49], similar issues in reproducibility compared to our study have been reported, even for simple dispersions in buffer. They concluded that SOPs are indispensable for obtaining reliable and comparable NP size data, and should be tailored to the specific test system, sufficiently detailed and verified by a larger number of laboratories, to enable reproducible performance [49,61].…”
Section: Discussionsupporting
confidence: 72%
“…However, for NMs special care has to be taken, because of possible batch-to-batch variation, contamination and long-term stability [46]. In our study, we have selected 50-nm amine-modified polystyrene NPs (PS-NH2) and 40-nm carboxyl-modified polystyrene NPs (PS-COOH), which are known to form stable dispersions when diluted in cell culture medium [47][48][49]. Furthermore, their impact on cells has been characterized in detail [22,26,48,[50][51][52].…”
Section: Choice Of Cytotoxicity Test and Materials Usedmentioning
confidence: 99%
“…For the other NMs, the individual particles are mostly aggregated, both in solution and in aerosols. A detailed discussion of DLS and DCS data from these as well from other QualityNano NMs is presented by Langevin et al [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Characterization of the PSNPs, by determining the hydrodynamic size and zeta-potential of the PSNPs in cell culture medium, showed that all 50 nm PSNP suspensions were stable during the exposure times in the experiments. The DLS method as used here has been evaluated in a inter laboratory testing project [ 31 ] to characterize the size of the PSNPs in water or DMEM + and it was found that the proteins present in the cell culture medium resulted in a signal indicating a hydrodynamic diameter of 27 ± 2 nm. The zeta-potential of all PSNPs in cell culture medium was comparable and stable over time, irrespective of the PSNP surface chemistry with a negative charge on the PSNPs’ surface results from the PSNPs, the proteins adsorbed on the surface of the PSNPs or from measuring protein aggregates of medium rather than PSNPs [ 9 ].…”
Section: Discussionmentioning
confidence: 99%